Perancangan UI/UX Aplikasi Mobile Pertolongan Pertama Dengan Metode Prototipe Interaksi Untuk Meningkatkan Respon Darurat - Nasution, Syahdin Alif Perdana; Wulandari, Heni; Arista, Ruly Dwi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Emergency accidents often happen unexpectedly and require quick first aid treatment. People's lack of knowledge about first aid often exacerbates the situation. This research aims to design the user interface (UI) and user experience (UX) of the mobile application “First Aid” using the interaction prototype method. This application is designed to provide guidance that is easy to understand and follow by ordinary people in providing first aid in emergency situations. With attractive visualizations and simple language, it is hoped that this application can bridge people's difficulties in understanding first aid procedures and increase responsiveness in emergency situations. First aid applications on smartphones can help people provide faster help during emergency situations. Based on this, this research specifically focuses on designing the user interface (UI) and user experience (UX) of a first aid application designed to provide fast and appropriate responses in emergency situations. The final result of this research is where the ui / UX design of the first aid application with the interaction prototype method to improve emergency response has a very positive impact, so that users / respondents rate it well with an average SUS score of 83.5 which gets Grade B Results For Ajective Ratings Get Excellent and Acceptability Get Acceptable, which is where the results obtained are good results in assessing an application that provides health services.